Tobacco Product Use and Associated Factors Among Middle and High School Students — United States, 2019 - Wang, Teresa W. (MMWR Surveill Summ, 2019)
PROBLEM/CONDITION: Tobacco use is the leading cause of preventable disease, disability, and death in the United States. Most tobacco product use begins during adolescence. In recent years, tobacco products have evolved to include various smoked, smokeless, and electronic products. PERIOD COVERED: 2019. DESCRIPTION OF SYSTEM: The National Youth Tobacco Survey (NYTS) is an annual, cross-sectional, school-based, self-administered survey of U.S. middle school (grades 6–8) and high school (grades 9–12) students. A three-stage cluster sampling procedure is used to generate a nationally representative sample of U.S. students attending public and private schools. NYTS is the only nationally representative survey of U.S. middle and high school students that focuses exclusively on tobacco use patterns and associated factors. NYTS is designed to provide national data on tobacco product use and has been conducted periodically during 1999–2009 and annually since 2011. Data from NYTS are used to support the design, implementation, and evaluation of comprehensive tobacco use prevention and control programs and to inform tobacco regulatory activities. Since its inception in 1999 through 2018, NYTS had been conducted via paper and pencil questionnaires. In 2019, NYTS for the first time was administered in schools using electronic data collection methods. CDC’s Office on Smoking and Health, in collaboration with the U.S. Food and Drug Administration’s (FDA’s) Center for Tobacco Products, analyzed data from the 2019 NYTS to assess tobacco product use patterns and associated factors among U.S. middle and high school students. Overall, 19,018 questionnaires were completed and weighted to represent approximately 27.0 million students. On the basis of self-reported grade level, this included 8,837 middle school questionnaires (11.9 million students) and 10,097 high school questionnaires (15.0 million students); 84 questionnaires with missing information on grade level were excluded from school-level analyses. RESULTS: In 2019, an estimated 53.3% of high school students (8.0 million) and 24.3% of middle school students (2.9 million) reported having ever tried a tobacco product. Current (past 30-day) use of a tobacco product (i.e., electronic cigarettes [e-cigarettes], cigarettes, cigars, smokeless tobacco, hookahs, pipe tobacco, and bidis [small brown cigarettes wrapped in a leaf]) was reported by 31.2% of high school students (4.7 million) and 12.5% of middle school students (1.5 million). E-cigarettes were the most commonly cited tobacco product currently used by 27.5% of high school students (4.1 million) and 10.5% of middle school students (1.2 million), followed in order by cigars, cigarettes, smokeless tobacco, hookahs, and pipe tobacco. Tobacco product use also varied by sex and race/ethnicity. Among current users of each tobacco product, the prevalence of frequent tobacco product use (on ≥20 days of the preceding 30 days) ranged from 16.8% of cigar smokers to 34.1% of smokeless tobacco product users. Among current users of each individual tobacco product, e-cigarettes were the most commonly used flavored tobacco product (68.8% of current e-cigarette users). Among students who reported ever having tried e-cigarettes, the three most commonly selected reasons for use were “I was curious about them” (55.3%), “friend or family member used them” (30.8%), and “they are available in flavors, such as mint, candy, fruit, or chocolate” (22.4%). Among never users of each individual tobacco product, curiosity and susceptibility (a construct that can help to identify future tobacco product experimentation or use) was highest for e-cigarettes (39.1% and 45.0%, respectively) and cigarettes (37.0% and 45.9%, respectively). Overall, 86.3% of students who reported contact with an assessed potential source of tobacco product advertisements or promotions (going to a convenience store, supermarket, or gas station; using the Internet; watching television or streaming services or going to the movies; or reading newspapers or magazines) reported exposure to marketing for any tobacco product; 69.3% reported exposure to e-cigarette marketing and 81.7% reported exposure to marketing for cigarettes or other tobacco products. Among all students, perceiving no harm or little harm from intermittent tobacco product use (use on some days but not every day) was 28.2% for e-cigarettes, 16.4% for hookahs, 11.5% for smokeless tobacco products, and 9.5% for cigarettes. Among current users of any tobacco product, 24.7% reported experiencing cravings to use tobacco products during the past 30 days and 13.7% reported wanting to use a tobacco product within 30 minutes of waking. Moreover, 57.8% of current tobacco product users reported they were seriously thinking about quitting the use of all tobacco products and 57.5% reported they had stopped using all tobacco products for ≥1 day because they were trying to quit. INTERPRETATION: In 2019, approximately one in four youths (23.0%) had used a tobacco product during the past 30 days. By school level, this represented approximately three in 10 high school students (31.2%) and approximately one in eight middle school students (12.5%). Since 2014, e-cigarettes have been the most commonly used tobacco product among youths. Importantly, more than half of current youth tobacco product users reported seriously thinking about quitting all tobacco products in 2019. However, established factors of use and initiation, including the availability of flavors, exposure to tobacco product marketing, curiosity and susceptibility, and misperceptions about harm from tobacco product use, remained prevalent in 2019 and continue to promote tobacco product use among youths. PUBLIC HEALTH ACTION: The continued monitoring of all forms of youth tobacco product use and associated factors through surveillance efforts including NYTS is important to the development of public health policy and action at national, state, and community levels. Everyone, including public health professionals, health care providers, policymakers, educators, parents, and others who influence youths, can help protect youths from the harms of all tobacco products. In addition, the comprehensive and sustained implementation of evidence-based tobacco control strategies, combined with FDA’s regulation of tobacco products, is important for reducing all forms of tobacco product use among U.S. youths.